A study on the effectiveness of promotional mix towards customer awareness at Pirate Park, Melaka / Mohd Faiz Ismail, Nor Hanisah Abd Manap and Norlyana Syafira Mohamad Razali - Ismail, Mohd Faiz; Abd Manap, Nor Hanisah; Mohamad Razali, Norlyana Syafira (2014)
Creating customer awareness is one of the most important aspect in park and recreation industry. The study focuses on the most effective promotional mix towards customer awareness. The aim of this study is to determine the most effective promotional mix and whether customers are aware of Pirate Park's products and services. To analyse the data, the researcher used SPSS software version 21. According to the results, the most effective promotional mix is personal selling (0.590), followed by public relation, advertising (0.446), direct selling (0.361), and sales promotion (0.296). After reviewing the literature, about 200 questionnaire was prepared but only 190 respondents participated.